Econometric wage and price models : assessing the impact of the economic stabilization program - Askin, A. Bradley; Kraft, John. (Lexington, Mass. : Lexington Books, 1974)
This book is another contribution to the literature on econometrics models of price and wage inflation and in particular on their application to evaluating the impact of the Nixon Administration's wag- price controls. Well over half of the text is devoted to a comparison of three quarterly models of the price and wage process, namely those constructed by Robert J.Gordon, by Otto Ecsktein and Roger Brinner and by Calvin Siebert and Mahmood Zaidi. These models are modified and then re-estimated using ordinary least square methods with a common set of data over an identical period (from the first quarter of 1955 to the second quarter of 1971).
Includes bibliographical references: p. 149-152.
rpm 23/04/2018
Loans
Keywords: Wage-price policy